“Fuerzas de Compresión de Resinas Bulk Fill a Fotocurado con Luz Led de Diferentes Potencias” - García Silva, Nataly Lizeth (2023)
ABSTRACT: This research aimed to analyze the resistance to compressive forces subjected to Bulk Fill resins with light curing of LED lamps of different powers using an experimental, observational, crosssectional in vitro study with a quantitative approach. Thirty samples with dimensions of 6mm diameter by 6mm high were made, divided into three groups: Group A- 3M Lamp 1550MW; Group B- Woodpecker Lamp 1350MW; Group C- Valo Lamp 1250 MW. The samples were subjected to compression in the Universal Tinius Olsen Model Super L 120 testing machine of the stress and vibration analysis laboratory of Escuela Politécnica Nacional. It is concluded that the compressive strength that gave the best result was Group A - Lamp 3M 1550MW, which presented greater compressive strength than the rest of the photocured resins subjected to different powers in this study. This shows that each lamp can provide a maximum value of more than 5000 N and 1200 lbf, but the lamps of group 2 on average. B and 3. C shows values notably lower than those of group 1